Theoretical investigation on the kinetics of dimethyl phosphoramidate with hydroxyl radicals - Aydogdu, Seyda; Hatipoglu, Arzu (ELSEVIER, 2019)
In this paper the reaction kinetics of dimethyl phosphoramidate with hydroxyl radical was investigated with Density Functional Theory. Geometry optimization and energy calculations of the reactants, the pre-reactive complexes, the transition states and the products were performed at the B3LYP/6-31G(d) basis set. The water effect was computed by using CPCM as the solvation model. Rate constants of all the possible reaction paths were calculated via Transition State Theory. The branching ratio for each of the reaction paths was calculated. The most probable reaction path was found the hydrogen abstraction from methyl group of dimethyl phosphoramidate.
Keywords: Dimethyl phosphoramidate; (OH)-O-center dot radical; DFT; rate constant; aqueous medium; PHOTOCATALYTIC OXIDATION; DEGRADATION; MECHANISMS; SIMULANTS; SURFACE; WATERS; GREECE; PHASE; MODEL; Chemistry